2022
DOI: 10.1021/acsami.2c13088
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Faraday Rotation of SrFe12O19 Hexaferrites Enhanced by Nb Doping

Abstract: The magneto-optical and dielectric behavior of M-type hexaferrites as permanent magnets in the THz band is essential for potential applications like microwave absorbers and antennas, while are rarely reported in recent years. In this work, single-phase SrFe12–x Nb x O19 hexaferrite ceramics were prepared by the conventional solid-state sintering method. Temperature dependence of dielectric parameters was investigated here to determine the relationship between dielectric response and magnetic phase transition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This improvement was achieved by lowering the natural resonance frequency ( f r ) and enhancing impedance matching. The substitution of the rare-earth element in place of divalent M 2+ in the M-type hexaferrite will enhance the reduction of Fe 3+ to Fe 2+ cation with the formation of oxygen vacancies [20,28]. The substitution of La 3+ in the M-type hexaferrite also reported that the conversion of Fe 3+ to Fe 2+ is enhanced with the generation of oxygen vacancies and affects the electronic and magnetic properties [29,30].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This improvement was achieved by lowering the natural resonance frequency ( f r ) and enhancing impedance matching. The substitution of the rare-earth element in place of divalent M 2+ in the M-type hexaferrite will enhance the reduction of Fe 3+ to Fe 2+ cation with the formation of oxygen vacancies [20,28]. The substitution of La 3+ in the M-type hexaferrite also reported that the conversion of Fe 3+ to Fe 2+ is enhanced with the generation of oxygen vacancies and affects the electronic and magnetic properties [29,30].…”
Section: Introductionmentioning
confidence: 97%
“…Zhu et al [19] reported that the electrical conduction and relaxation behaviours of BaFe 10.2 Sc 1.8 O 19 M-type hexaferrite is contributed mainly by the movable oxygen vacancies. The electronic and magnetic characteristics of M-type hexaferrite were also reported to be affected by introducing oxygen vacancies or defects [20,21]. These oxygen vacancies or defects can be created through synthesis conditions (temperature and pressure) or cationic substitution methods.…”
Section: Introductionmentioning
confidence: 99%